Dispositional forgiveness buffers paranoia following interpersonal transgression. Issue 3 (27th July 2022) - Ellett, Lyn; Foxall, Anna; Wildschut, Tim; Chadwick, Paul
Abstract: Objective: To test a novel proposition that dispositional forgiveness has the unrecognized benefit of buffering feelings of paranoia following negative interpersonal experiences and interpersonal transgressions. Methods: In Study 1 ( N = 128), we used an experimental paradigm, the Prisoner's Dilemma Game (PDG), to test the premise that an interpersonal transgression increases state paranoia. Study 2 ( N = 180) used a longitudinal design to test the central proposition that dispositional forgiveness buffers state paranoia following naturally occurring difficult (vs pleasant) interpersonal events. Study 3 ( N = 102) used a novel experimental paradigm to determine the causal effect of manipulating forgiveness on paranoia. Results: In Study 1, interpersonal transgressions in the PDG increased paranoia. In Study 2, paranoia was higher following difficult (rather than pleasant) events, and higher levels of dispositional forgiveness moderated the negative effect of difficult events on paranoia. In Study 3, there was a causal effect of forgiveness on (reduced) paranoia. Conclusions: This is the first evidence that (1) interpersonal transgressions increase paranoia, (2) high dispositional forgiveness moderates the deleterious effect of interpersonal transgression on paranoia, and (3) dispositional forgiveness is causally related to less paranoia.